UV-Curable Quantum Dot Formulations

JP2025505372APending Publication Date: 2025-02-26SHOEI CHEM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024542997
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-19
Filing Date
2023-01-18
Publication Date
2025-02-26

Smart Images

  • Figure 2025505372000001_ABST
    Figure 2025505372000001_ABST
Patent Text Reader

Abstract

A patterned film is provided that includes nanostructures and one or more UV curable monomers, the nanostructure film including about 60 wt% to about 95 wt% nanostructures. Also provided are methods of making the patterned film and electroluminescent devices including the patterned film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is in the field of nanostructures. A patterned film is provided that includes nanostructures and one or more UV-curable monomers. Summary of the Invention

[0002] [Brief Summary of the Invention] An ultraviolet (UV) cured patterned film deposited on a substrate is provided, the patterned film comprising about 60 wt % to about 95 wt % nanostructures and one or more UV curable monomers.

[0003] In some embodiments, the one or more UV curable monomers are selected from the group consisting of poly(methyl (meth)acrylate), poly(ethylene glycol phenyl (meth)acrylate), poly(di(ethylene glycol) methyl ether (meth)acrylate), poly(diethylene glycol monoethyl ether acrylate), poly(ethylene glycol methyl ether (meth)acrylate), poly(1,3-butylene glycol di(meth)acrylate), poly(polyethylene glycol di(meth)acrylate), poly(1,6-hexanediol di(meth)acrylate), poly(1,3-butylene ... acrylate), poly(isobomylar acrylate), poly(tetrahydrofurfuryl acrylate), poly(lauryl acrylate), poly(tricyclodecane dimethanol diacrylate), poly(glycerol triacrylate), poly(1,1,1-trimethylolpropane triacrylate), poly(pentaerythritol tetraacrylate), poly(bistrimethylolpropane tetraacrylate), poly(dipentaerythritol pentaacrylate), poly(pentaerythritol tri ... poly(1,1,1-trimethylolpropane trimethacrylate), poly(pentaerythritol tetraacrylate), poly(isobornyl methacrylate), poly(tetrahydrofurfuryl methacrylate), poly(lauryl methacrylate), poly(tricyclodecane dimethanol dimethacrylate), poly(glycerol trimethacrylate), poly(1,1,1-trimethylolpropane trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(bistrimethylolpropane Poly(pentaerythritol tetramethacrylate), poly(dipentaerythritol pentamethacrylate), poly(pentaerythritol trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(trimethylolpropane trimethacrylate), poly(dipentaerythritol pentamethacrylate ester), poly(1,6-hexanediol dimethacrylate), poly(1,4-butanediol diacrylate), poly(1,9-nonanediol diacrylate), poly(1,4-butanediol dimethacrylate), poly(1,9-nonanediol dimethacrylate), or a combination thereof.

[0004] In some embodiments, the film further includes one or more photoinitiators.

[0005] In some embodiments, the film comprises: (a) depositing onto a substrate a solution comprising nanostructures, one or more UV-curable monomers, a photoinitiator, and one or more solvents, wherein a weight ratio of the nanostructures to the one or more UV-curable monomers is from about 20:1 to about 1.5:1; (b) evaporating the one or more solvents to obtain a film comprising the nanostructures, the one or more UV curable monomers, and a photoinitiator; (c) applying a photomask to the substrate; (d) irradiating the substrate with ultraviolet light; (e) removing the photomask; and (f) washing the substrate with one or more solvents to obtain a patterned film; Manufactured by.

[0006] In some embodiments, the weight ratio of nanostructures to one or more UV curable monomers is from about 14:1 to about 6:1.

[0007] In some embodiments, the one or more UV curable monomers are acrylate monomers.

[0008] In some embodiments, the acrylate monomer is 1,6-hexanediol diacrylate.

[0009] In some embodiments, the film obtained in (b) comprises about 0.1 wt % to about 0.3 wt % of a photoinitiator based on the total weight of the one or more UV-curable monomers.

[0010] In some embodiments, the photoinitiator is ethylphenyl(2,4,6-trimethylbenzoyl)phosphinate (TPO-L).

[0011] In some embodiments, the irradiation in (d) is about 530 mJ / cm 2 of 365 nm UV light.

[0012] In some embodiments, the one or more solvents is toluene.

[0013] In some embodiments, the nanostructures are quantum dots.

[0014] In some embodiments, the nanostructures comprise polyethylene glycol-based ligands.

[0015] In some embodiments, the film is insoluble in toluene.

[0016] In some embodiments, the film has a quantum yield (QY) of about 35% to about 50%.

[0017] Also provided is an electroluminescent device comprising the above-described film.

[0018] In some embodiments, the device has a maximum external quantum efficiency (EQE) of about 3.75% to about 5.25%.

[0019] In some embodiments, the device has a thermal conductivity of about 4,000 cd / m 2 to about 9,000 cd / m 2 It has a maximum brightness of .

[0020] In some embodiments, the device has a lifetime of about 8.5 hours to about 20.5 hours at 1,000 nits.

[0021] In some embodiments, the device has a lifetime of about 500 hours to about 1,300 hours at 100 nits.

[0022] In some embodiments, the film pattern is a pixelated pattern.

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate the present embodiments and, together with the description, explain the principles of the embodiments and enable one skilled in the relevant art to make and use the embodiments. [Brief description of the drawings]

[0024] [Figure 1A] 1A and 1B are two line graphs showing current density as a function of voltage for electroluminescent devices including a thinner emissive layer (FIG. 1A) and a thicker emissive layer (FIG. 1B), where the emissive layer includes an ultraviolet (UV) cured quantum dot (QD) film with various amounts of 1,6-hexanediol diacrylate (HDDA). [Figure 1B] 1A and 1B are two line graphs showing current density as a function of voltage for electroluminescent devices including a thinner emissive layer (FIG. 1A) and a thicker emissive layer (FIG. 1B), where the emissive layer includes an ultraviolet (UV) cured quantum dot (QD) film with various amounts of 1,6-hexanediol diacrylate (HDDA). [Diagram 2] FIG. 2 is a schematic showing a network of polymerized HDDA formed around the QDs in the close-packed emissive layer (EML). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] All technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs, unless otherwise defined. The following definitions are supplementary to those of ordinary skill in the art and are directed to this application, and are not to be attributed to related or unrelated cases, such as commonly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be actually used for testing, the preferred materials and methods are described herein. Therefore, the terms used herein are only for describing specific embodiments, and are not intended to be limiting.

[0026] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "nanostructure" includes a plurality of such nanostructures.

[0027] As used herein, the term "about" indicates that a given quantity value varies by ±10% of that value. For example, "about 100 nm" encompasses a range of sizes from 90 nm to 110 nm.

[0028] A "nanostructure" is a structure having at least one region or characteristic dimension that is less than about 500 nm in dimension. In some embodiments, the nanostructure has a dimension that is less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm, e.g., 1-10 nm. Typically, the region or characteristic dimension is along the smallest axis of the structure. Examples of such structures include nanowires, nanorods, nanotubes, branched nanostructures, nanotetrapods, tripods, bipods, nanocrystals, nanodots, quantum dots, nanoparticles, and the like. Nanostructures can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or combinations thereof. In some embodiments, each of the three dimensions of the nanostructure has a dimension that is less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.

[0029] The term "heterostructure", when used with respect to nanostructures, refers to a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of the nanostructure comprises a first material type and a second region of the nanostructure comprises a second material type. In certain embodiments, the nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material, where the different material types are distributed radially, for example, relative to the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. The shell may, but does not necessarily, completely cover adjacent materials to be considered a shell or for the nanostructure to be considered a heterostructure. For example, a nanocrystal characterized by a core of one material covered by small islands of a second material is a heterostructure. In other embodiments, the different material types are distributed at different locations within the nanostructure, for example, along the long axis of a nanowire or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure may comprise entirely different materials, or the different regions may comprise a base material (eg, silicon) with different dopants or different concentrations of the same dopant.

[0030] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section perpendicular to a first axis of the nanostructure, where the first axis has the greatest length difference with respect to the second and third axes (the second and third axes being the two axes whose lengths are most nearly equal to each other). The first axis is not necessarily the longest axis of the nanostructure. For example, for a disk-shaped nanostructure, the cross section will be a substantially circular cross section perpendicular to the short axis of the disk. If the cross section is not circular, the diameter is the average of the long and short axes of the cross section. For elongated nanostructures such as nanowires or nanostructures with high aspect ratios, the diameter is measured across a cross section perpendicular to the longest axis of the nanowire. For spherical nanostructures, the diameter is measured from one end to the other through the center of the sphere.

[0031] The term "crystalline" or "substantially crystalline", when used in reference to a nanostructure, refers to the fact that the nanostructure typically exhibits long-range order across one or more dimensions of its structure. One of skill in the art will appreciate that the term "long-range order" depends on the absolute size of a particular nanostructure, since the order of a single crystal cannot extend beyond the boundaries of the crystal. In this case, "long-range ordering" refers to substantial order across at least the majority of the dimensions of the nanostructure. In some cases, the nanostructure may have an oxide or other coating, or may include a core and at least one shell. In such cases, it will be understood that the oxide, shell, or other coating may, but need not, exhibit such order (e.g., may be amorphous, polycrystalline, or otherwise). In such cases, the phrases "crystalline", "substantially crystalline", "substantially monocrystalline", or "monocrystalline" refer to the central core of the nanostructure (excluding any coating layers or shells). As used herein, the terms "crystalline" or "substantially crystalline" are intended to encompass structures that contain various defects, stacking faults, atomic substitutions, and the like, so long as the structures exhibit substantial long-range order (e.g., order over at least about 80% of the length of at least one axis of the nanostructure or its core). Furthermore, it will be understood that the interface between the core and exterior of a nanostructure, or the interface between the core and an adjacent shell, or the interface between a shell and a second adjacent shell, may include non-crystalline regions and be amorphous. This does not prevent a nanostructure from being crystalline or substantially crystalline as defined herein.

[0032] The term "single crystal" when used in reference to a nanostructure indicates that the nanostructure is substantially crystalline and comprises substantially a single crystal. When used in reference to a nanostructure heterostructure comprising a core and one or more shells, "single crystal" indicates that the core is substantially crystalline and comprises substantially a single crystal.

[0033] A "nanocrystal" refers to a nanostructure that is substantially monocrystalline. Thus, a nanocrystal has at least one region or characteristic dimension that is less than about 500 nm in dimension. In some embodiments, a nanocrystal has a dimension that is less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm, e.g., 1-10 nm. The term "nanocrystal" is intended to encompass substantially monocrystalline nanostructures that contain various defects, stacking faults, atomic substitutions, and the like, as well as substantially monocrystalline nanostructures that are free of such defects, stacking faults, and substitutions. In the case of nanocrystal heterostructures that include a core and one or more shells, the core of the nanocrystal is typically substantially monocrystalline, although the shells need not be. In some embodiments, each of the three dimensions of the nanocrystal has a dimension that is less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.

[0034] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum or exciton confinement. Quantum dots can be substantially homogeneous in material properties or, in certain embodiments, can be heterogeneous, e.g., comprising a core and at least one shell. The optical properties of quantum dots can be affected by their particle size, chemical composition, and / or surface composition, and can be determined by suitable optical tests available in the art. The ability to tune the nanocrystal size, e.g., in the range between about 1 nm and about 15 nm, allows photon emission across the entire optical spectrum, providing highly versatile color rendering.

[0035] A "ligand" is a molecule that can interact (either strongly or weakly) with one or more facets of a nanostructure, for example, through covalent bonds, ionic bonds, van der Waals bonds, or other molecular interactions with the surface of the nanostructure.

[0036] "Photoluminescence quantum yield" (PLQY), for example, is the ratio of photons emitted to photons absorbed by a nanostructure or population of nanostructures. As known in the art, quantum yield is typically determined by comparative methods using well-characterized standards with known quantum yield values.

[0037] "Peak emission wavelength" (PWL) is the wavelength at which the radiometric emission spectrum of a light source is at a maximum.

[0038] As used herein, the term "shell" refers to material deposited on a core or on a previously deposited shell of the same or different composition resulting from a single deposition of shell material. The exact shell thickness depends on the material, precursor input and conversion and may be reported in nanometers or monolayers. As used herein, "target shell thickness" refers to the intended shell thickness used to calculate the amount of precursor required. As used herein, "actual shell thickness" refers to the amount of shell material actually deposited after synthesis and can be measured by methods known in the art. As an example, the actual shell thickness can be measured by comparing particle diameters determined from transmission electron microscope (TEM) images of nanocrystals before and after shell synthesis.

[0039] The term "full width at half maximum" (FWHM) as used herein is a measure of the size distribution of nanoparticles. The emission spectrum of nanoparticles generally has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM and gives insight into the size distribution of the particles. A smaller FWHM means a narrower size distribution of the quantum dot nanocrystals. The FWHM also depends on the peak emission wavelength.

[0040] The term "half width at maximum" (HWHM) as used herein is a measure of the size distribution of nanoparticles extracted from UV-vis spectroscopy curves. The HWHM on the low-energy side of the first exciton absorption peak can be used as a suitable indicator of size distribution, with smaller HWHM values ​​corresponding to narrower size distributions.

[0041] [Nanostructure Core] The core of the nanostructures used in the present invention can be made of any suitable material, preferably an inorganic material, more preferably an inorganic conductive or semiconducting material. Suitable semiconducting materials include any type of semiconductor, including II-VI semiconductors, III-V semiconductors, IV-VI semiconductors, and Group IV semiconductors. Suitable semiconductor materials include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, BN, BP, BAs, AlN, A1P, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, and combinations thereof.

[0042] Synthesis of II-VI nanostructures is described in U.S. Patent Nos. 6,225,198, 6,322,901, 6,207,229, 6,607,829, 6,861,155, 7,060,243, 7,125,605, 7,374,824, 7,566,476, 8,101,234, 8,158,193, and U.S. Patent Application Publication Nos. 2011 / 0262752 and 2011 / 0263062. In some embodiments, the core is a II-VI nanocrystal selected from the group consisting of ZnO, ZnSe, ZnS, ZnTe, CdO, CdSe, CdS, CdTe, HgO, HgSe, HgS, and HgTe. In some embodiments, the core is a nanocrystal selected from the group consisting of ZnSe, ZnS, CdSe, and CdS.

[0043] Although II-VI nanostructures such as CdSe and CdS quantum dots can exhibit desirable luminescence behavior, issues such as the toxicity of cadmium limit the applications in which such nanostructures can be used. Therefore, less toxic alternatives with favorable luminescence properties are highly desirable. III-V nanostructures in general, and InP-based nanostructures in particular, offer the best-known alternative to cadmium-based materials due to their compatible emission range.

[0044] Regarding the synthesis of InP-based nanostructures, for example, Xie, R., et al., 「Colloidal InP nanocrystals as efficient emitters covering blue to near-infrared」 J. Am. Chem. Soc. 729: 15432-15433 (2007), Micic, O.I., et al., 「Core-shell quantum dots of lattice-matched ZnCdSe2 shells on InP cores: Experiment and theory」 J. Phys. Chem. B 704: 12149-12156 (2000), Liu, Z., et al., 「Coreduction colloidal synthesis of III-V nanocrystals: The case of InP」 Angew. Chem. Int. Ed. Engl. 47: 3540-3542 (2008), Li, L. et al., 「Economic synthesis of high quality InP nanocrystals using calcium phosphide as the phosphorus precursor」 Chem. Mater. 20: 2621-2623 (2008), D. Battaglia and X. Peng, 「Formation of high quality InP and InAs nanocrystals in a noncoordinating solvent」 Nano Letters 2: 1027-1030 (2002), Kim, S., et al., 「Highly luminescent InP / GaP / ZnS nanocrystals and their application to white light-emitting diodes」 J. Am. Chem. Soc. 737: 3804-3809 (2012), Nann, T., et al., 「Water splitting by visible light: A nanophotocathode for hydrogen production」Angew. Chem. Int. Ed. 49: 1574-1577 (2010)、Borchert, H., et al., 「Investigation of ZnS passivated InP nanocrystals by XPS」 Nano Letters 2: 151-154 (2002)、L. Li and P. Reiss, 「One-pot synthesis of highly luminescent InP / ZnS nanocrystals without precursor injection」 J. Am. Chem. Soc. 130: 11588-11589 (2008)、Hussain, S., et al. 「One-pot fabrication of high-quality InP / ZnS (core / shell) quantum dots and their application to cellular imaging」 Chemphyschem. 10: 1466-1470 (2009)、Xu, S., et al., 「Rapid synthesis of high-quality InP nanocrystals」 J. Am. Chem. Soc. 128: 1054-1055 (2006)、Micic, O.I., et al., 「Size-dependent spectroscopy of InP quantum dots」 J. Phys. Chem. B 101: 4904-4912 (1997)、Haubold, S., et al., 「Strongly luminescent InP / ZnS core-shell nanoparticles」 Chemphyschem. 5: 331-334 (2001)、CrosGagneux, A., et al., 「Surface chemistry of InP quantum dots: A comprehensive study」 J. Am. Chem. Soc.132: 18147-18157 (2010), Micic, OI, et al., “Synthesis and characterization of InP, GaP, and GaInP2quantum dots” J. Phys. Chem. 99: 7754-7759 (1995), Guzelian, AA, et al., “Synthesis of size-selected, surface- "passivated InP nanocrystals" J. Phys. Chem. 100: 7212-7219 (1996), Lucey, DW, et al., "Monodispersed InP quantum dots prepared by colloidal chemistry in a non-coordinating solvent" Chem. Mater. 17: 3754-3762 (2005), Lim, J., et al. al., “InP@ZnSeS, core@composition gradient shell "Quantum dots with enhanced stability," Chem. Mater. 23: 4459-4463 (2011), and Zan, F., et al., "Experimental studies on blinking behavior of single InP / ZnS quantum dots: Effects of synthetic conditions and UV irradiation," J. Phys. Chem. C 116: 394-3950 (2012). However, these efforts have met with limited success in producing InP nanostructures with quantum yields.

[0045] In some embodiments, the InP core is doped. In some embodiments, the dopant of the nanocrystalline core includes a metal, including one or more transition metals. In some embodiments, the dopant is a transition metal selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, and combinations thereof. In some embodiments, the dopant includes a non-metal. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP, or GaAs.

[0046] In some embodiments, the cores are purified prior to deposition of the shell, hi some embodiments, the cores are filtered to remove precipitates from the core solution.

[0047] In some embodiments, the diameter of the InP core is determined using quantum confinement. Quantum confinement in zero-dimensional nanocrystals, such as quantum dots, arises from the spatial confinement of electrons within the crystallite boundaries. Quantum confinement can be observed when the diameter of the material is as large as the de Broglie wavelength of the wave function. The electronic and optical properties of nanoparticles deviate significantly from those of bulk materials. When the confinement size is large compared to the particle's wavelength, the particle behaves as if it were free. In this state, the band gap remains at its original energy due to the continuum of energy states. However, as the confinement size decreases to a certain limit (typically the nanoscale), the energy spectrum becomes discontinuous. As a result, the band gap becomes size dependent.

[0048] In some embodiments, the nanostructures are cadmium-free. As used herein, the term "cadmium-free" contemplates that the nanostructures contain less than 100 ppm cadmium by weight. The Restriction of Hazardous Substances (RoHS) compliant definition states that cadmium should not exceed 0.01% by weight (100 ppm) in raw homogenous precursor materials. The cadmium level in the cadmium-free nanostructures of the present invention is limited by the trace metal concentration in the precursor material. The trace metal (including cadmium) concentration in the precursor material of the cadmium-free nanostructures can be measured at the parts per billion (ppb) level by inductively coupled plasma mass spectrometry (ICP-MS) analysis. In some embodiments, the "cadmium-free" nanostructures contain less than about 50 ppm, less than about 20 ppm, less than about 10 ppm, or less than about 1 ppm cadmium.

[0049] [shell] In some embodiments, the nanostructure core comprises one or more shells. Examples of materials for preparing the shell include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, and combinations thereof.

[0050] In some embodiments, the shell is a mixture of at least two of the zinc source, the selenium source, the sulfur source, the tellurium source, and the cadmium source. In some embodiments, the shell is a mixture of two of the zinc source, the selenium source, the sulfur source, the tellurium source, and the cadmium source. In some embodiments, the shell is a mixture of three of the zinc source, the selenium source, the sulfur source, the tellurium source, and the cadmium source. In some embodiments, the shell is a mixture of zinc and sulfur, zinc and selenium, zinc and sulfur and selenium, zinc and tellurium, zinc and tellurium and sulfur, zinc and tellurium and selenium, zinc and cadmium and sulfur, zinc and cadmium and selenium, cadmium and sulfur, cadmium and selenium, cadmium and zinc, cadmium and zinc and sulfur, cadmium and zinc and selenium, or cadmium and zinc and sulfur and selenium. In some embodiments, the shell is a mixture of zinc and selenium. In one embodiment, the shell is a mixture of zinc and sulfur.

[0051] Exemplary core / shell luminescent nanostructures include, but are not limited to, CdSe / ZnSe and InP / ZnSe (referred to as core / shell).

[0052] In one embodiment, the shell comprises ZnSe. The thickness of the shell can be controlled by varying the amount of precursors provided. For a given shell thickness, at least one of the precursors is suitably provided in an amount such that a shell of the given thickness is obtained when the growth reaction is substantially complete. In certain embodiments, the molar ratio of the zinc source to the selenium source is from about 0.01:1 to about 1:1.5, from about 0.01:1 to about 1:1.25, from about 0.01:1 to about 1:1, from about 0.01:1 to about 1:1, from about 0.01:1 to about 1:0.75, from about 0.01:1 to about 1:0.5, from about 0.01:1 to about 1:0.25, from about 0.01:1 to about 1:0.05, from about 0.05:1 to about 1:1.5, from about 0.05:1 to about 1:1.25, from about 0.05:1 to about 1:1, from about 0.05:1 to about 1:0.75, from about 0.05:1 to about 1:0.5, from about 0.05:1 to about 1 :0.25, about 0.25:1 to about 1:1.5, about 0.25:1 to about 1:1.25, about 0.25:1 to about 1:1, about 0.25:1 to about 1:0.75, about 0.25:1 to about 1:0.5, about 0.5:1 to about 1:1.5, about 0.5:1 to about 1:1.25, about 0.5:1 to about 1:1, about 0.5:1 to about 1:0.75, about 0.75:1 to about 1:1.5, about 0.75:1 to about 1:1.25, about 0.75:1 to about 1:1:1, about 1:1 to about 1:1.5, about 1:1 to about 1:1.25, or about 1:1.25 to about 1:1.5.

[0053] The thickness of the ZnSe shell layer can be controlled by varying the amounts of zinc and selenium sources provided and / or by using longer reaction times and / or higher temperatures, with at least one source being provided in an amount such that a layer of a predetermined thickness is obtained when the growth reaction is substantially complete.

[0054] The thickness of the ZnSe thin shell can be determined using techniques known to those of skill in the art. In some embodiments, the thickness of the inner thin shell is determined by comparing the average diameter of the nanostructure before and after the addition of the inner thin shell. In some embodiments, the average diameter of the nanostructure before and after the addition of the inner thin shell is determined by TEM. In some embodiments, the ZnSe shell has a thickness of about 0.01 nm to about 0.35 nm, about 0.01 nm to about 0.3 nm, about 0.01 nm to about 0.25 nm, about 0.01 nm to about 0.2 nm, about 0.01 nm to about 0.1 nm, about 0.01 nm to about 0.05 nm, about 0.05 nm to about 0.35 nm, about 0.05 nm to about 0.3 nm, about 0.05 nm to about 0.25 nm, about 0.05 nm to about 0.2 nm, The thickness is about 0.05 nm to about 0.1 nm, about 0.1 nm to about 0.35 nm, about 0.1 nm to about 0.3 nm, about 0.1 nm to about 0.25 nm, about 0.1 nm to about 0.2 nm, about 0.2 nm to about 0.35 nm, about 0.2 nm to about 0.3 nm, about 0.2 nm to about 0.25 nm, about 0.25 nm to about 0.35 nm, about 0.25 nm to about 0.3 nm, or about 0.3 nm to about 0.35 nm.

[0055] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate, zinc hexanoate, zinc octanoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or mixtures thereof. In some embodiments, the zinc source is zinc oleate.

[0056] In some embodiments, the selenium source is an alkyl-substituted selenourea. In some embodiments, the selenium source is a phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octaneselenol, 1-dodecaneselenol, selenophenol, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenourea, and mixtures thereof. In certain embodiments, the selenium source is tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, or tri(tert-butyl)phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.

[0057] In some embodiments, the ZnSe shell is synthesized in the presence of at least one nanostructure ligand. The ligand can, for example, increase the miscibility of the nanostructure in a solvent or polymer (allowing the nanostructure to be dispersed throughout the composition so that the nanostructure does not aggregate), increase the quantum yield of the nanostructure, and / or preserve the luminescence of the nanostructure (e.g., when the nanostructure is incorporated into a UV-curable monomer). In some embodiments, the ligand(s) for the InP core synthesis and the ligand(s) for the shell synthesis are the same. In some embodiments, the ligand(s) for the core synthesis and the ligand(s) for the shell synthesis are different. After synthesis, the ligands on the nanostructure surface can be exchanged for different ligands with other desirable properties. Examples of ligands are disclosed in U.S. Patent Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435, and U.S. Patent Application Publication No. 2008 / 0118755.

[0058] Ligands suitable for the synthesis of the shell are known to those skilled in the art. In some embodiments, the ligand is a fatty acid selected from the group consisting of lauric acid, caproic acid, myristic acid, palmitic acid, stearic acid, and oleic acid. In some embodiments, the ligand is an organophosphine or organophosphine oxide selected from trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), diphenylphosphine (DPP), triphenylphosphine oxide, and tributylphosphine oxide. In some embodiments, the ligand is an amine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand is oleic acid.

[0059] In one embodiment, the nanostructure composition comprises an InP / ZnSe / ZnS core-shell nanostructure, where at least one of the ZnSe and ZnS shells has a thickness between 0.7 nm and 3.5 nm, the nanostructure exhibits a photoluminescence quantum yield between 60 and 99%, the nanostructure exhibits a full width at half maximum between 35 nm and 45 nm, and the nanostructure exhibits an OD450 / peak between about 1.0 and about 3.0. Such nanostructures and methods for their manufacture are disclosed in U.S. Patent Application Publication Nos. 2017 / 0306227 and 2018 / 0199007.

[0060] In some embodiments, the nanostructure comprises a core comprising indium phosphide and at least two shells, at least one of the shells comprising zinc, the nanostructure exhibits a photoluminescence quantum yield of about 94% to about 100%, and the nanostructure has a full width at half maximum of less than 45 nm. In some embodiments, the nanostructure is an InP / ZnSe / ZnS nanostructure. Such nanostructures and methods for their manufacture are disclosed in U.S. Patent Application Publication No. 2020 / 0325396.

[0061] In some embodiments, the nanostructure composition comprises a core-shell nanostructure surface treated with zinc acetate and zinc fluoride. In some embodiments, the present disclosure provides a nanostructure composition comprising an InP / ZnSe core-shell nanostructure. In some embodiments, the ZnSe shell has a thickness of about 0.01 nm to about 5 nm. In some embodiments, the nanostructure is a quantum dot. Such nanostructures and methods for making the same are disclosed in U.S. Patent Application Publication No. 2021 / 0013377.

[0062] In some embodiments, the nanostructure composition comprises ZnSe having one or more shell layers. 1-x Te x In some embodiments, the nanostructure comprises a core surrounded by at least one shell, the core being ZnSe 1-x Te xIt includes, where \(0 \lt x \lt 1\), and at least one shell is selected from the group consisting of ZnS, ZnSe, ZnTe, and their alloys, and the full width at half maximum (FWHM) of the nanostructure is from about 20 nm to about 30 nm. Such nanostructures and their manufacturing methods are disclosed in U.S. Patent Application Publication No. 2021 / 0047563.

[0063] In some embodiments, the nanostructure includes a nanocrystal core and at least one shell, and the at least one shell includes at least one metal fluoride of the following formula (I). MF4 (I) Where M = Zr, Hf, or Ti. In some embodiments, the nanostructure is (a) a core containing ZnSe, at least one shell containing ZnS, and at least one shell containing HfF4, or (b) a core containing ZnSe 1-x Te x (where \(0 \leq x \leq 1\)), at least one shell containing ZnSe, and at least one shell containing ZnS, and at least one shell containing HfF4. Such nanostructures and their manufacturing methods are disclosed in U.S. Patent Application Publication No. 2021 / 0277307.

[0064] In some embodiments, the nanostructure includes a core surrounded by at least one shell, and the core contains ZnSe 1-x Tex, where \(0 \lt x \lt 1\), at least one shell contains ZnS or ZnSe, and the full width at half maximum (FWHM) of the nanostructure is from about 10 nm to about 30 nm. In some embodiments, the nanostructure is a ZnSe 1-x Te x / ZnSe / ZnS core / shell nanostructure. Such nanostructures and their manufacturing methods are disclosed in U.S. Patent Application Publication No. 2019 / 0390109.

[0065] In some embodiments, the nanostructure comprises a nanocrystalline core and at least one shell disposed on the core, the at least one shell comprising ZnS and a fluoride. In some embodiments, the nanostructure comprises a core comprising ZnSe and at least one shell comprising ZnS and ZnF2, a core comprising ZnSe and at least one shell comprising ZnSe and at least one shell comprising ZnS and ZnF2, a core comprising ZnSe and at least one shell comprising ZnS and ZnF2, <x<1であるZnSe 1-x Te x and at least one shell comprising ZnS and ZnF2, or <x<1であるZnSe 1-x Te x and at least one shell comprising ZnSe, and at least one shell comprising ZnS and ZnF2. Such nanostructures and methods for making them are disclosed in U.S. Patent Application Publication No. 2021 / 0009900.

[0066] In some embodiments, the nanostructures include at least one fluoride-containing ligand attached to the surface of the nanostructure (wherein the fluoride-containing ligand is selected from the group consisting of fluorozincate, tetrafluoroborate, and hexafluorophosphate) or a fluoride anion attached to the surface of the nanostructure (wherein the nanostructure composition exhibits a photoluminescence quantum yield of between about 70% and about 90%). Such nanostructures and methods for making them are disclosed in U.S. Patent Application Publication No. 2020 / 0299575.

[0067] In some embodiments, the nanostructure comprises Ag, In, Ga, and S (AIGS). In some embodiments, the nanostructure has a peak emission wavelength (PWL) in the range of 480-545 nm, at least about 80% of the emission is band edge emission, and the nanostructure exhibits a quantum yield (QY) of 80-99.9%. Such nanostructures and methods for their manufacture are disclosed in U.S. Patent No. 10,927,294.

[0068] In some embodiments, the nanostructures include at least one poly(alkylene oxide) ligand attached to the surface of the nanostructure. Such ligands are disclosed in U.S. Patent No. 11,041,071.

[0069] [Films, Devices, and Applications] The population of nanostructures is embedded in a UV-curable monomer that forms a film. This film can be used to manufacture nanostructure phosphors and / or can be incorporated into devices such as LEDs, backlights, downlights, other display or lighting units, or optical filters. Exemplary phosphors and lighting units can produce a specific color light, for example, by incorporating a population of nanostructures that have an emission maximum at or near a desired wavelength, or can produce a wide color gamut by incorporating two or more different populations of nanostructures with different emission maxima. A variety of suitable matrices are known in the art. See, for example, U.S. Pat. No. 7,068,898 and U.S. Patent Application Publication Nos. 2010 / 0276638, 2007 / 0034833, and 2012 / 0113672. Exemplary nanostructured phosphor films, LEDs, backlight units, and the like are described, for example, in U.S. Patent Application Publication Nos. 2010 / 0276638, 2012 / 0113672, 2008 / 0237540, 2010 / 0110728, and 2010 / 0155749, and U.S. Patent Nos. 7,374,807, 7,645,397, 6,501,091, and 6,803,719.

[0070] In some embodiments, the nanostructure film is used to form a display device. As used herein, a display device refers to any system having an illuminated display. Such devices include, but are not limited to, devices that include liquid crystal displays (LCDs), televisions, computers, mobile phones, smartphones, personal digital assistants (PDAs), game consoles, e-readers, digital cameras, and the like.

[0071] In some embodiments, the present disclosure provides a nanostructure molded article comprising: (a) a first conductive layer; (b) a second conductive layer; and (c) a nanostructure layer between the first conductive layer and the second conductive layer, the nanostructure layer comprising a population of nanostructures embedded in one or more UV curable monomers.

[0072] In some embodiments, the present disclosure provides a nanostructure film comprising: (a) at least one population of nanostructures; and (b) at least one UV-curable monomer;

[0073] As used herein, the term "embedded" is used to indicate that the nanostructures are encapsulated or encased within one or more UV curable monomers. In some embodiments, the nanostructures are uniformly distributed throughout the one or more UV curable monomers. In some embodiments, the nanostructures are distributed according to an application specific uniformity distribution function.

[0074] In this disclosure, a solvent-based nanostructure formulation is provided that includes one or more UV-curable monomers and a photoinitiator. After deposition, the nanostructure / monomer film may be crosslinked by UV irradiation. Surprisingly, the UV-crosslinked nanostructure film results in functional electroluminescent devices with high efficiency and brightness, even though the polyacrylate network is insulating. Devices using UV-crosslinked nanostructure films have long operational lifetimes. The UV-curable nanostructure films can be patterned by using a photomask and appropriate washing conditions to remove the unexposed segments.

[0075] Nanostructured films in QD-LEDs can undergo structural changes during device fabrication or operation that can affect device performance. For example, solution deposition of a layer on top of the QDs can dissolve and remove the nanostructures or their ligands, resulting in loss of light emission. Thermal annealing of the device can promote interlayer diffusion and create leakage paths. Application of an electric field can cause ionic dissociation and migration. Formation of a crosslinked network between or around the QDs improves the stability of QD-LEDs by suppressing these structural changes.

[0076] The fabrication of displays using electroluminescent QDs requires pixel patterning. Inkjet printing has low throughput at high resolution and cannot achieve the fine feature sizes, e.g., <5 pm, required for microdisplays for AR / VR applications. Although several photolithographic techniques for patterning QDs for electroluminescence have been reported, none have performed satisfactorily. Mixing QDs with photoresist results in high operating voltages due to the low QD loadings used (10–40 wt%), low efficiency due to poor compatibility between photoresist and QDs, and harsh development conditions using strong bases. Lift-off methods using a photoresist layer separate from the QDs do not introduce insulating material into the QD film, but they introduce additional process steps and are also inefficient and have poor film uniformity due to the development conditions. Additives such as photoacid generators and bis(azido) crosslinkers, which modify the ligand chemistry of the QD surface upon UV irradiation, seem promising for convenient processing and low additive loading, but suffer from reduced efficiency for materials that rely on ligand surface passivation, i.e., non-giant shell QDs. The present invention overcomes these drawbacks.

[0077] In some embodiments, the nanostructure film comprises one or more UV curable monomers, hi some embodiments, the one or more UV curable monomers are UV curable acrylates. In some embodiments, the UV curable acrylate is poly(methyl (meth)acrylate), poly(ethylene glycol phenyl (meth)acrylate), poly(di(ethylene glycol) methyl ether (meth)acrylate), poly(diethylene glycol monoethyl ether acrylate), poly(ethylene glycol methyl ether (meth)acrylate), poly(1,3-butylene glycol di(meth)acrylate), poly(polyethylene glycol di(meth)acrylate), poly(1,6-hexanediol diacrylate), poly(isobomylar acrylate), poly(tetrahydrofurfuryl acrylate), poly(lauryl acrylate), poly(tricyclodecane dimethanol diacrylate), poly(glycerol triacrylate), poly(1,1,1-trimethylolpropane triacrylate), poly(pentaerythritol tetraacrylate), poly(bistrimethylolpropane tetraacrylate), poly(dipentaerythritol pentaacrylate). ), poly(pentaerythritol triacrylate), poly(pentaerythritol tetraacrylate), poly(trimethylolpropane triacrylate), poly(dipentaerythritol pentaacrylate ester), poly(isobornyl methacrylate), poly(tetrahydrofurfuryl methacrylate), poly(lauryl methacrylate), poly(tricyclodecane dimethanol dimethacrylate), poly(glycerol trimethacrylate), poly(1,1,1-trimethylolpropane trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(bistrimethylolpropane tetramethacrylate), poly(dipentaerythritol pentamethacrylate), poly(pentaerythritol trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(trimethylolpropane trimethacrylate), poly(dipentaerythritol pentamethacrylate ester), poly(1,6-hexanediol dimethacrylate), poly(1,The poly(1,4-butanediol diacrylate), poly(1,9-nonanediol diacrylate), poly(1,4-butanediol dimethacrylate), and poly(1,9-nonanediol dimethacrylate), or a combination thereof.

[0078] In some embodiments, the nanostructure film comprises between about 1 wt% and about 25 wt% of one or more UV curable monomers. In some embodiments, the nanostructure film includes from about 1 wt% to about 5 wt%, from about 1 wt% to about 10 wt%, from about 1 wt% to about 15 wt%, from about 1 wt% to about 20 wt%, from about 1 wt% to about 25 wt%, from about 5 wt% to about 10 wt%, from about 5 wt% to about 15 wt%, from about 5 wt% to about 20 wt%, from about 5 wt% to about 25 wt%, from about 10 wt% to about 15 wt%, from about 10 wt% to about 20 wt%, from about 10 wt% to about 25 wt%, from about 15 wt% to about 20 wt%, from about 15 wt% to about 25 wt%, or from about 20 wt% to about 25 wt% of one or more UV curable monomers.

[0079] In some embodiments, the nanostructure film comprises nanostructures and a UV curable monomer, and the weight ratio of nanostructures to UV curable monomer is about 20:1 to about 1.5:1. In some embodiments, the nanostructure film comprises nanostructures and a UV curable monomer, and the weight ratio of nanostructures to UV curable monomer is about 20:1 to about 1.5:1, about 15:1 to about 1.5:1, about 10:1 to about 1.5:1, about 5:1 to about 1.5:1, about 20:1 to about 5:1, about 15:1 to about 5:1, about 10:1 to about 5:1, about 20:1 to about 10:1, about 15:1 to about 10:1, or about 20:1 to about 15:1.

[0080] In some embodiments, the nanostructure film comprises about 60 wt% to about 95 wt% nanostructures. In some embodiments, the nanostructure film comprises about 60 wt% to about 70%, about 60 wt% to about 75%, about 60 wt% to about 80%, about 60 wt% to about 85%, about 60 wt% to about 90%, about 70 wt% to about 75%, about 70 wt% to about 80%, about 70 wt% to about 85%, about 70 wt% to about 9 ... The nanostructures may comprise about 75 wt% to about 95%, about 75 wt% to about 80%, about 75 wt% to about 85%, about 75 wt% to about 90%, about 75 wt% to about 95%, about 80 wt% to about 85%, about 80 wt% to about 90%, about 80 wt% to about 95%, about 85 wt% to about 90%, about 85 wt% to about 95%, or about 90% to about 95%.

[0081] In some embodiments, the nanostructure film further comprises one or more barrier layers immediately adjacent to the nanostructure film that have low oxygen and moisture permeability to protect the nanostructures from degradation.

[0082] In some embodiments, the nanostructure film is formed from a solution containing one or more photoinitiators, hi some embodiments, the photoinitiators are triazine-based compounds, acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, oxime-based compounds, or combinations thereof.

[0083] Examples of triazine compounds include 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2 -biphenyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphthol-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthol-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-(piperonyl)-s-triazine, or 2,4-bis(trichloromethyl)-6-(4'-methoxystyryl)-s-triazine.

[0084] Examples of acetophenones include 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropinophenone, pt-butyltrichloroacetophenone, pt-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-l-(4-(methylthio)phenyl)-2-morpholinopropan-1-one, and 2-benzyl-2-dimethylamino-l-(4-morpholinophenyl)-butan-l-one.

[0085] Examples of benzophenone-based compounds include benzophenone, benzoyl benzoate, benzoylmethyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, and 3,3'-dimethyl-2-methoxybenzophenone.

[0086] Examples of thioxanthone compounds include thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone.

[0087] Examples of the benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzyl dimethyl ketal.

[0088] Examples of oxime compounds include 2-(o-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione and 1-(o-acetyloxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone.

[0089] The photopolymerization initiator may be a carbazole-based compound, a diketone-based compound, a sulfonium borate-based compound, a diazo-based compound, a biimidazole-based compound, or the like, in addition to a photopolymerization initiator.

[0090] In some embodiments, the photoinitiator is 2,4,6-trimethylbenzoyldiphenylphosphinate (TPO-L).

[0091] In some embodiments, the nanostructure film is formed from a solution containing about 0.05 wt% to about 0.5 wt% of a photoinitiator based on the weight of one or more UV curable monomers present in the solution. In some embodiments, the nanostructure film is formed from a solution containing about 0.05 wt% to about 0.1 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.3 wt%, about 0.05 wt% to about 0.4 wt%, about 0.05 wt% to about 0.5 wt%, about 0.1 ...3 wt%, about 0.1 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0.2 wt%, about 0.05 wt% to about 0 Contains 0.2 wt%, about 0.1 wt% to about 0.3 wt%, about 0.1 wt% to about 0.4 wt%, about 0.1 wt% to about 0.5 wt%, about 0.2 wt% to about 0.3 wt%, about 0.2 wt% to about 0.4 wt%, about 0.2 wt% to about 0.5 wt%, about 0.3 wt% to about 0.4 wt%, about 0.3 wt% to about 0.5 wt%, or 0.4 wt% to about 0.5 wt%.

[0092] In some embodiments, the nanostructure film can be formed by mixing a composition comprising the nanostructures, one or more UV curable monomers, and a solvent (e.g., a photoresist) and casting the nanostructure composition mixture onto a substrate.

[0093] In some embodiments, the nanostructure film has a photoluminescence quantum yield (QY) of about 35% to about 50%, about 35% to about 60%, about 35% to about 70%, about 35% to about 80%, about 35% to about 90%, about 35% to about 100%, about 50% to about 60%, about 50% to about 70%, about 50% to about 80%, about 50% to about 90%, about 50% to about 100%, about 60% to about 70%, about 60% to about 80%, about 60% to about 90%, about 60% to about 100%, about 70% to about 80%, about 70% to about 90%, about 70% to about 100%, about 80% to about 90%, about 80% to about 100%, or about 90% to about 100%.

[0094] In some embodiments, the population of nanostructures is used to form a nanostructure molded article. In some embodiments, the nanostructure molded article is a liquid crystal display (LCD) or a light emitting diode (LED). In some embodiments, the nanostructure composition is used to form a light emitting layer of a lighting device. The lighting device can be used in a wide variety of applications, such as flexible electronics, touch screens, monitors, televisions, cell phones, and any other high definition display. In some embodiments, the lighting device is a light emitting diode or a liquid crystal display. In some embodiments, the lighting device is a quantum dot light emitting diode (QLED). Examples of QLEDs are disclosed in U.S. Patent Application Serial No. 15 / 824,701, which is incorporated by reference herein in its entirety. In some embodiments, the core shell nanostructure is InP / ZnSe or ZnTeSe / ZnSe / ZnS. In some embodiments, the molded article does not include a separate barrier layer to protect the nanostructures from oxygen and / or moisture.

[0095] In some embodiments, the present disclosure provides a lighting device including: (a) a first conductive layer; (b) a second conductive layer; and (c) an emissive layer between the first conductive layer and the second conductive layer, the emissive layer comprising at least one population of nanostructures and one or more UV curable monomers.

[0096] In some embodiments, the core-shell nanostructure is CdSe / ZnSe, ZnTeSe / ZnSe / ZnS, or InP / ZnSe.

[0097] In some embodiments, the light emitting layer is a nanostructured film.

[0098] In some embodiments, the lighting device comprises a first conductive layer, a second conductive layer, and a light emitting layer, the light emitting layer being disposed between the first conductive layer and the second conductive layer, In some embodiments, the light emitting layer is a thin film comprising one or more populations of nanostructures and one or more UV curable monomers.

[0099] In some embodiments, the lighting device comprises additional layers between the first conductive layer and the second conductive layer, such as a hole injection layer, a hole transport layer, an electron transport layer, etc. In some embodiments, the hole injection layer, the hole transport layer, and the electron transport layer are thin films. In some embodiments, the layers are laminated on a substrate.

[0100] When a voltage is applied to the first conductive layer and the second conductive layer, holes injected into the first conductive layer migrate to the light-emitting layer through the hole injection layer and / or the hole transport layer, and electrons injected from the second conductive layer migrate to the light-emitting layer through the electron transport layer. The holes and electrons recombine in the light-emitting layer to generate excitons. In some embodiments, the hole transport layer comprises poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] (TFB).

[0101] The substrate may be any substrate commonly used in the manufacture of lighting devices. In some embodiments, the substrate is a transparent substrate, such as glass. In some embodiments, the substrate is a flexible material, such as polyimide, or a flexible and transparent material, such as polyethylene terephthalate. In some embodiments, the substrate is about 0.1 mm to about 2 mm thick. In some embodiments, the substrate is a glass substrate, a plastic substrate, a metal substrate, or a silicon substrate.

[0102] In some embodiments, a first conductive layer is disposed on a substrate. In some embodiments, the first conductive layer is a stack of conductive layers. In some embodiments, the first conductive layer has a thickness of about 50 nm to about 250 nm. In some embodiments, the first conductive layer is deposited as a thin film by using any known deposition technique, such as, for example, sputtering or e-beam evaporation. In some embodiments, the first conductive layer comprises indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), zinc oxide (ZnO), magnesium (Mg), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag), silver (Ag), gold (Au), or mixtures thereof. In some embodiments, the first conductive layer is an anode.

[0103] In some embodiments, additional layers can be sandwiched between the first and second conductive layers. In some embodiments, the first conductive layer functions as the anode of the device and the second conductive layer functions as the cathode of the device. In some embodiments, the second conductive layer is a metal, such as aluminum. In some embodiments, the second conductive layer has a thickness between about 100 nm and about 150 nm. In some embodiments, the second conductive layer represents a stack of conductive layers. For example, the second conductive layer can include a layer of silver sandwiched between two layers of ITO (ITO / Ag / ITO).

[0104] In some embodiments, the second conductive layer comprises indium tin oxide (ITO), indium zinc oxide (IZO), titanium dioxide, tin oxide, zinc sulfide, silver (Ag), or a mixture thereof.

[0105] In some embodiments, the lighting device further comprises a semiconducting polymer layer. In some embodiments, the semiconducting polymer layer functions as a hole injection layer. In some embodiments, the semiconducting polymer layer is deposited on the first conductive layer. In some embodiments, the semiconducting polymer layer is deposited by vacuum deposition, spin coating, printing, casting, slot-die coating, or Langmuir-Blodgett (LB) deposition. In some embodiments, the semiconducting polymer layer has a thickness between about 20 nm and about 60 nm.

[0106] In some embodiments, the semiconducting polymer layer comprises copper phthalocyanine, 4,4',4''-tris[(3-methylphenyl)phenylamino]triphenylamine (m-MTDATA), 4,4',4''-tris(diphenylamino)triphenylamine (TDATA), 4,4',4''-tris[2-naphthyl(phenyl)amino]triphenylamine (2T-NATA), polyaniline / dodecylbenzenesulfonic acid, poly(3,4-ethylenedioxythiophene) / polystyrenesulfonic acid (PEDOT / PSS), polyaniline / camphorsulfonic acid, or polyaniline / poly(4-styrenesulfonic acid).

[0107] In some embodiments, the lighting device further comprises a transport layer for facilitating transport of electrons and holes under the influence of an electric field generated between the first conductive layer and the second conductive layer. In some embodiments, the lighting device further comprises a first transport layer associated with the first conductive layer. In some embodiments, the first transport layer acts as a hole transport layer (and an electron and / or exciton blocking layer). In some embodiments, the first transport layer is deposited on the first conductive layer. In some embodiments, the first transport layer is deposited on the semiconducting polymer layer. In some embodiments, the first transport layer has a thickness of about 20 nm to about 50 nm. In some embodiments, the first transport layer is substantially transparent to visible light.

[0108] In some embodiments, the first transport layer comprises a material selected from the group consisting of amines, triarylamines, thiophenes, carbazoles, phthalocyanines, porphyrins, or mixtures thereof. In some embodiments, the first transport layer comprises N,N'-di(naphthalen-l-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl))diphenylamine)], and poly(9-vinylcarbazole).

[0109] In some embodiments, the lighting device further comprises a second transport layer. In some embodiments, the second transport layer acts as an electron transport layer (and hole and / or exciton blocking layer). In some embodiments, the second transport layer contacts the light-emitting layer. In some embodiments, the second transport layer is disposed between the light-emitting layer and the second conductive layer. In some embodiments, the second transport layer has a thickness of about 20 nm to about 50 nm. In some embodiments, the second transport layer is substantially transparent to visible light.

[0110] In some embodiments, the second transport layer is an electron transport layer.

[0111] When the polarity of the first and second conductive layers is reversed, the roles of the first and second transport layers are reversed.

[0112] In some embodiments, the lighting device comprises at least one electron transport layer. In some embodiments, the lighting device is a quantum dot light emitting diode.

[0113] In some embodiments, the electron transport layer has a thickness of about 20 nm to about 50 nm. In some embodiments, the electron transport layer has a thickness of about 20 nm to about 50 nm, about 20 nm to about 40 nm, about 20 nm to about 30 nm, about 30 nm to about 50 nm, about 30 nm to about 40 nm, or about 40 nm to about 50 nm.

[0114] In some embodiments, the electron transport layer comprises zinc oxide.

[0115] In some embodiments, the electron transport layer comprises zinc magnesium oxide.

[0116] In some embodiments, the lighting device may be about 2% to about 3%, about 2% to about 4%, about 2% to about 5%, about 2% to about 6%, about 2% to about 7%, about 2% to about 8%, about 2% to about 9%, about 2% to about 10%, about 3% to about 4%, about 3% to about 5%, about 3% to about 6%, about 3% to about 7%, about 3% to about 8%, about 3% to about 9%, about 3% to about 10%, about 4% to about 5%, about 4% to about 6%, about 4% to about 7%, about has an external quantum efficiency (EQE) of 4% to about 8%, about 4% to about 9%, about 4% to about 10%, about 5% to about 6%, about 5% to about 7%, about 5% to about 8%, about 5% to about 9%, about 5% to about 10%, about 6% to about 7%, about 6% to about 8%, about 6% to about 9%, about 6% to about 10%, about 7% to about 8%, about 7% to about 9%, about 7% to about 10%, about 8% to about 9%, about 8% to about 10%, or about 9% to about 10%.

[0117] In some embodiments, the lighting device has a power output of about 4000 cd / m 2 ~about 6000cd / m 2 , about 4000cd / m 2 ~About 9000cd / m 2 , about 4000cd / m 2 ~Approx. 12000cd / m2, approx. 6000cd / m 2 ~About 9000cd / m 2 , about 6000cd / m 2 ~About 12000cd / m 2 , or about 9000 cd / m 2 ~About 12000cd / m 2 It has a maximum brightness of .

[0118] In some embodiments, the lifetime of the lighting device at 1000 nits is about 8.5 hours to about 20.5 hours, about 6 hours to about 10 hours, about 6 hours to about 13 hours, about 6 hours to about 16 hours, about 6 hours to about 20 hours, about 6 hours to about 24 hours, about 10 hours to about 13 hours, about 10 hours to about 16 hours, about 10 hours to about 20 hours, about 10 hours to about 24 hours, about 13 hours to about 16 hours, about 13 hours to about 20 hours, about 13 hours to about 24 hours, about 16 hours to about 20 hours, about 16 hours to about 24 hours, or about 20 hours to about 24 hours.

[0119] In some embodiments, the lifetime of the lighting device at 100 nits is about 500 hours to about 1,300 hours, about 400 hours to about 700 hours, about 400 hours to about 900 hours, about 400 hours to about 1,300 hours, about 400 hours to about 1,600 hours, about 700 hours to about 900 hours, about 700 hours to about 1,300 hours, about 700 hours to about 1,600 hours, about 900 hours to about 1,300 hours, about 900 hours to about 1,600 hours, or about 1,300 hours to about 1,600 hours.

[0120] In some embodiments, the nanostructure film is incorporated into a glass LCD display device. The LCD display device may include a nanostructure film formed directly on a light guide plate (LGP) without the need for an intermediate substrate or barrier layer. In some embodiments, the nanostructure film may be a thin film. In some embodiments, the nanostructure film may be 500 pm or less, 100 pm or less, or 50 pm or less in thickness. In some embodiments, the nanostructure film is a thin film with a thickness of about 15 pm or less. In some embodiments, the core-shell nanostructure is CdSe / ZnSe, ZnTeSe / ZnSe / ZnS, or InP / ZnSe.

[0121] The light guide plate may include an optical cavity with one or more sides, including at least the top surface, made of glass. Glass provides excellent resistance to impurities, including moisture and air. Additionally, glass can be formed as a thin substrate while maintaining structural rigidity. Thus, the light guide plate may be formed at least in part from a glass surface to provide a substrate with sufficient barrier and structural properties.

[0122] In some embodiments, a nanostructure film can be formed on a light guide plate. In some embodiments, the nanostructure film includes one or more populations of nanostructures and one or more UV curable monomers. The nanostructure film can be formed on the light guide plate by any method known in the art, such as wet coating, painting, spin coating, screen printing, etc. After deposition, the one or more UV curable monomers of the nanostructure film can be cured. In some embodiments, the one or more UV curable monomers of the nanostructure film can be partially cured, further processed, and finally cured. The nanostructure film can be deposited as a layer or as separate layers, and the separate layers can include various properties. The width and height of the nanostructure film can be any desired dimension depending on the size of the display panel of the display device. For example, the nanostructure film can have a relatively small surface area in small display device embodiments such as watches and phones. Alternatively, the nanostructure film can have a large surface area in large display device embodiments such as televisions and computer monitors.

[0123] In some embodiments, an optically transparent substrate is formed on the nanostructure film by any method known in the art, such as vacuum deposition, vapor deposition, etc. The optically transparent substrate can be appropriately configured to provide environmental sealing to the underlying layers and / or structures of the nanostructure film. In some embodiments, light blocking elements can be included in the optically transparent substrate. In some embodiments, the light blocking elements can be included in a second polarizing filter that can be disposed between the substrate and the nanostructure film. In some embodiments, the light blocking elements can be, for example, dichroic filters that can reflect primary light (e.g., blue light, ultraviolet light, or a combination of ultraviolet and blue light) while transmitting secondary light. The light blocking elements can include specific ultraviolet filter components to remove unconverted ultraviolet light from the red and green subpixels and / or ultraviolet light from the blue subpixels.

[0124] In some embodiments, the nanostructure film is incorporated into the display device by an "on-chip" arrangement. As used herein, "on-chip" refers to the placement of the nanostructures in the LED cup. In some embodiments, the nanostructures are dissolved in a resin or fluid and filled into the LED cup. In some embodiments, the LED cup does not further comprise a barrier layer to protect the nanostructures from oxygen and / or moisture.

[0125] In some embodiments, the nanostructures are incorporated into the display device in a "near-chip" configuration, which as used herein refers to coating the top surface of an LED cluster with nanostructures such that the emitted light passes through the nanostructure film.

[0126] In some embodiments, the present invention provides a display device including: (a) a display panel that emits a first light; (b) a backlight unit configured to provide the first light to the display panel; and (c) a color filter including at least one pixel region that includes a color conversion layer.

[0127] In some embodiments, the color filter comprises at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 pixel regions. In some embodiments, when blue light is incident on the color filter, red light, white light, green light, and / or blue light can be emitted through the pixel regions, respectively. In some embodiments, the color filter is described in U.S. Patent Application Publication No. 2017 / 153366.

[0128] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to a first color of light. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to blue light.

[0129] In some embodiments, the display device comprises 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 color conversion layers. In some embodiments, the display device comprises one color conversion layer comprising the nanostructures described herein. In some embodiments, the display device comprises two color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises three color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises four color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises at least one red color conversion layer, at least one green color conversion layer, and at least one blue color conversion layer.

[0130] In some embodiments, the color conversion layer has a thickness of about 3 pm to about 10 pm, about 3 pm to about 8 pm, about 3 pm to about 6 pm, about 6 pm to about 10 pm, about 6 pm to about 8 pm, or about 8 pm to about 10 pm. In some embodiments, the color conversion layer has a thickness of about 3 pm to about 10 pm.

[0131] [Film manufacturing method] The present disclosure provides a method for producing a patterned film comprising nanostructures and one or more UV curable monomers. In some embodiments, the method for producing the patterned film comprises: (a) depositing onto a substrate a solution comprising nanostructures, one or more UV-curable monomers, a photoinitiator, and one or more solvents, wherein the weight ratio of nanostructures to one or more UV-curable monomers is from about 20:1 to about 1.5:1; (b) evaporating the one or more solvents to obtain a film comprising the nanostructures, the one or more UV curable monomers, and a photoinitiator; (c) applying a photomask to the substrate obtained in (b); (d) irradiating the substrate with ultraviolet light; (e) removing the photomask; and (f) washing the substrate with one or more solvents to obtain a patterned film; Includes.

[0132] In some embodiments, the one or more UV curable monomers are UV curable acrylate monomers. In some embodiments, the UV curable acrylate monomers are selected from methyl (meth)acrylate, ethylene glycol phenyl (meth)acrylate, di(ethylene glycol) methyl ether (meth)acrylate, diethylene glycol monoethyl ether acrylate, ethylene glycol methyl ether (meth)acrylate, 1,3-butylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and 1,6-hexanediol diacrylate, or combinations thereof.

[0133] In some embodiments, the film resulting from (b) comprises from about 1 wt % to about 25 wt % of one or more UV-curable monomers. In some embodiments, the film obtained in (b) comprises from about 1 wt % to about 5 wt %, from about 1 wt % to about 10 wt %, from about 1 wt % to about 15 wt %, from about 1 wt % to about 20 wt %, from about 1 wt % to about 25 wt %, from about 5 wt % to about 10 wt %, from about 5 wt % to about 15 wt %, from about 5 wt % to about 20 wt %, from about 5 wt % to about 25 wt %, from about 10 wt % to about 15 wt %, from about 10 wt % to about 20 wt %, from about 10 wt % to about 25 wt %, from about 15 wt % to about 20 wt %, from about 15 wt % to about 25 wt %, or from about 20 wt % to about 25 wt % of one or more UV-curable monomers.

[0134] In some embodiments, the film obtained in (b) comprises nanostructures and UV curable monomers, and the weight ratio of the nanostructures to the UV curable monomers is about 20:1 to about 1.5:1. In some embodiments, the film obtained in (b) comprises nanostructures and UV curable monomers, and the weight ratio of the nanostructures to the UV curable monomers is about 20:1 to about 1.5:1, about 15:1 to about 1.5:1, about 10:1 to about 1.5:1, about 5:1 to about 1.5:1, about 20:1 to about 5:1, about 15:1 to about 5:1, about 10:1 to about 5:1, about 20:1 to about 10:1, about 15:1 to about 10:1, or about 20:1 to about 15:1.

[0135] In some embodiments, the film obtained in (b) comprises about 60 wt% to about 95 wt% of the nanostructures. In some embodiments, the solution comprises about 60 wt% to about 70%, about 60 wt% to about 75%, about 60 wt% to about 80%, about 60 wt% to about 85%, about 60 wt% to about 90%, about 70 wt% to about 75%, about 70 wt% to about 80%, about 70 wt% to about 85%, about 70 wt% to about 90%, about 70 wt% to about 90%. 5%, about 75 wt% to about 80%, about 75 wt% to about 85%, about 75 wt% to about 90%, about 75 wt% to about 95%, about 80 wt% to about 85%, about 80 wt% to about 90%, about 80 wt% to about 95%, about 85 wt% to about 90%, about 85 wt% to about 95%, or about 90% to about 95% nanostructures.

[0136] Examples of solvents include toluene, benzene, xylene, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, chloroform, chlorobenzene, cyclohexane, hexane, heptane, octane, hexadecane, undecane, decane, dodecane, octadecane, tetradecane, butyl ether, dipropylene glycol monomethyl ether acetate (DPMA), polyglycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC), propylene glycol methyl ether acetate (PGMEA), 1-tetralone, 3-phenoxytoluene, acetophenone, 1-methoxynaphthalene, n-octylbenzene, n-nonylbenzene, 4-methylanisole, n -decylbenzene, p-diisopropylbenzene, pentylbenzene, tetralin, cyclohexylbenzene, chloronaphthalene, 1,4-dimethylnaphthalene, 3-isopropylbiphenyl, p-methylcumene, dipentylbenzene, o-diethylbenzene, m-diethylbenzene, p-diethylbenzene, 1,2,3,4-tetramethylbenzene, 1,2,3,5-tetramethylbenzene, 1,2,4,5-tetramethylbenzene, butylbenzene, dodecylbenzene, 1-methylnaphthalene, 1,2,4-trichlorobenzene, diphenyl ether, diphenylmethane, 4-isopropylbiphenyl, benzyl benzoate, 1,2-bis(3,4-dimethylphenyl)ethane, 2-isopropylnaphthalene, dibenzyl ether, cyclododecene, butyl acetate, hexyl acetate, or combinations thereof.

[0137] The solvent can be evaporated by heating the substrate, placing the substrate under reduced pressure, or a combination thereof.

[0138] The photomask shields a portion of the deposited nanostructures and one or more UV-curable monomers from exposure to UV light. The photomask can be of any shape suitable for forming a desired pattern on the substrate after UV exposure and rinsing. In some embodiments, the shape of the photomask results in a pixelated pattern after UV exposure and rinsing.

[0139] The substrate can be irradiated by any ultraviolet radiation source known in the art. Examples of ultraviolet radiation sources include mercury vapor lamps, fluorescent lamps, LED lamps, etc. In some embodiments, the wavelength of the ultraviolet light is about 365 nm. In some embodiments, the wavelength of the ultraviolet light is about 253 nm.

[0140] In some embodiments, the irradiation in (d) has a dose of about 500 mJ / cm 2 ~Approx. 550mJ / cm 2 In some embodiments, the irradiation in (d) has a dose of about 100 mJ / cm. 2 ~about 200mJ / cm 2 , about 100mJ / cm 2 ~About 300mJ / cm 2 , about 100mJ / cm 2 ~about 400mJ / cm 2 , about 100mJ / cm 2 ~about 500mJ / cm 2 , about 100mJ / cm 2 ~about 600mJ / cm 2 , about 100mJ / cm 2 ~about 700mJ / cm 2 , about 100mJ / cm 2 ~about 800mJ / cm 2 , about 100mJ / cm 2 ~Approx. 900mJ / cm 2 , about 100mJ / cm 2 ~Approx. 1000mJ / cm 2 , about 200mJ / cm 2 ~About 300mJ / cm 2 , about 200mJ / cm 2 ~about 400mJ / cm 2 , about 200mJ / cm 2~about 500 mJ / cm 2 、about 200 mJ / cm 2 ~about 600 mJ / cm 2 、about 200 mJ / cm 2 ~about 700 mJ / cm 2 、about 200 mJ / cm 2 ~about 800 mJ / cm 2 、about 200 mJ / cm 2 ~about 900 mJ / cm 2 、about 200 mJ / cm 2 ~about 1000 mJ / cm 2 、about 300 mJ / cm 2 ~about 400 mJ / cm 2 、about 300 mJ / cm 2 ~about 500 mJ / cm 2 、about 300 mJ / cm 2 ~about 600 mJ / cm 2 、about 300 mJ / cm 2 ~about 700 mJ / cm 2 、about 300 mJ / cm 2 ~about 800 mJ / cm 2 、about 300 mJ / cm 2 ~about 900 mJ / cm 2 、about 300 mJ / cm 2 ~about 1000 mJ / cm 2 、about 400 mJ / cm 2 ~about 500 mJ / cm 2 、about 400 mJ / cm 2 ~about 600 mJ / cm 2 、about 400 mJ / cm 2 ~about 700 mJ / cm 2 、about 400 mJ / cm 2 ~about 800 mJ / cm 2 、about 400 mJ / cm 2 ~about 900 mJ / cm 2 、about 400 mJ / cm 2 ~about 1000 mJ / cm 2 、about 500 mJ / cm 2 ~about 600 mJ / cm 2 、about 500 mJ / cm 2 ~about 700 mJ / cm 2 、about 500 mJ / cm 2 ~about 800 mJ / cm 2, about 500mJ / cm 2 ~Approx. 900mJ / cm 2 , about 500mJ / cm 2 ~Approx. 1000mJ / cm 2 , about 600mJ / cm 2 ~about 700mJ / cm 2 , about 600mJ / cm 2 ~about 800mJ / cm 2 , about 600mJ / cm 2 ~Approx. 900mJ / cm 2 , about 600mJ / cm 2 ~Approx. 1000mJ / cm 2 , about 700mJ / cm 2 ~about 800mJ / cm 2 , about 700mJ / cm 2 ~Approx. 900mJ / cm 2 , about 700mJ / cm 2 ~Approx. 1000mJ / cm 2 , about 800mJ / cm 2 ~Approx. 900mJ / cm 2 , about 800mJ / cm 2 ~Approx. 1000mJ / cm 2 , or about 900 mJ / cm 2 ~Approx. 1000mJ / cm 2 It is.

[0141] In some embodiments, the irradiation in (d) has a dose of about 530 mJ / cm 2 In some embodiments, the irradiation in (d) has a dose of about 50 mJ / cm. 2 , about 100mJ / cm 2 , about 150mJ / cm 2 , about 200mJ / cm 2 , about 250mJ / cm 2 , about 300mJ / cm 2 , about 350mJ / cm 2 , about 400mJ / cm 2 , about 450mJ / cm 2 .Approx. 500mJ / cm 2 , about 550mJ / cm 2 , about 600mJ / cm 2 , about 650mJ / cm 2 , about 700mJ / cm 2, about 750mJ / cm 2 , about 800mJ / cm 2 , about 850mJ / cm 2 , about 900mJ / cm 2 , about 950mJ / cm 2 , or about 1000 mJ / cm 2 It is. EXAMPLES

[0142] Example 1: UV-cured HDDA QD films with high QD loading Here, we show that formulations with high QD loadings in the range of 80-95 wt% (or 5-20 wt% acrylate) result in UV-curable QD films with good performance in electroluminescent devices. Because the highly QD-loaded acrylate formulations are not fluid, an evaporable non-reactive organic solvent is used as a carrier for solution deposition. These formulations use PEG-based ligands on the QD surface to enhance the dispersibility of the QDs in the acrylate monomer.

[0143] Table 1 shows the effect of the loading of acrylate (specifically, 1,6-hexanediol diacrylate, HDDA) in wt% on blue ZnTeSe / ZnSe / ZnS QDs on UV irradiation (365 nm, 530–630 mJ / cm 2 The effect of HDDA on the solubility of films after irradiation is shown in Figure 1. Films were drop cast from toluene, dried, irradiated, and then immersed in toluene. Below a loading of HDDA of 5 wt%, the irradiated films were soluble in toluene. For loadings of HDDA between 5 and 20 wt%, the cured films became increasingly insoluble, as judged by low or no emission in the toluene used to immerse the cured films. Furthermore, optimizing the amount of photoinitiator TPO-L (wt% relative to HDDA) resulted in solid-state quantum yields (QYs) comparable to those of control samples containing neither acrylate nor initiator.

[0144] [Table 1]

[0145] Example 2: Electroluminescent Device Comprising UV-Curable HDDA QD Film with High QD Loading as the Emitting Layer We tested the performance of UV-curable HDDA QD films with high QD loading as an emissive layer (EML) in electroluminescent devices (structure: ITO / PEDOT:PSS / SH112 / QD / ZnMgO / LiF / Al). Since polyacrylate is an insulator, it was expected that charge transport and injection to the QDs would be hindered. The JV characteristics in Figures 1A and 1B confirm this effect. The current density decreases with increasing HDDA content, and the effect is more pronounced for thicker EMLs, implying lower mobility in the crosslinked EML.

[0146] Despite the lower current density, the devices were still functional. Unexpectedly, the efficiency and lifetime were improved, as shown in Table 2. The external quantum efficiency (EQE) was improved from 1.6–2.6% for EMLs without HDDA to 4.0–4.9% for EMLs with HDDA. The maximum luminance achieved (7 V, end of sweep) was of the same order of magnitude for the crosslinked samples. This is because the higher efficiency is achieved at lower current densities. The lifetime was significantly increased by the UV treatment to initiate crosslinking, e.g., the sample with 10 wt% HDDA loading showed an almost order of magnitude increase in T50 from 2.8 h to 20.1 h at 1000 nits. No efficiency tradeoff was observed with this lifetime improvement.

[0147] [Table 2]

[0148] Without being bound to any particular theory, a hypothesized mechanism for the lifetime enhancement is shown diagrammatically in Figure 2. Polymerization of HDDA in the QD film forms a network around the QDs, restricting the mobility of the QDs and ligands, which prevents ligand desorption during subsequent processing and manipulation and helps maintain the surface passivation of the QDs.

[0149] UV-induced immobilization of QDs also allows for patterning with a photomask and pattern development by washing away the QD / HDDA mixture in non-irradiated areas with an appropriate solvent. Pixel patterns with well-defined, photoluminescent 100 × 300 pm features were formed using red InP / ZnSe / ZnS QDs with PEG ligand and 10 wt% HDDA. After UV exposure, ethanol was used to remove the QD / HDDA from non-irradiated areas.

[0150] It is understood that the Detailed Description section is intended to be used to interpret the claims, and not the Abstract and Summary sections. The Abstract and Summary sections may set forth one or more exemplary embodiments of the invention contemplated by the inventor, but are not all inclusive, and thus are not intended to limit the scope of the invention and the appended claims in any way.

[0151] The present invention has been described above with the aid of functional building blocks illustrating the implementation of certain functions and relationships thereof. The boundaries of these functional building blocks have been arbitrarily defined herein for convenience of description. Alternative boundaries may be defined so long as the specified functions and relationships thereof are appropriately performed.

[0152] The above description of specific embodiments fully reveals the general nature of the present invention, so that those skilled in the art can easily modify and / or adapt such specific embodiments for various applications without undue experimentation and without departing from the general concept of the present invention. Therefore, such modifications and adaptations are intended to be within the meaning and range of equivalents of the disclosed embodiments, based on the teaching and guidance presented herein. It should be understood that the terms or phrases in this specification are for the purpose of description and not for the purpose of limitation, as they should be interpreted by those skilled in the art in light of the teaching and guidance.

[0153] The breadth and scope of the present invention should not be limited by any of the above-described exemplary embodiments, but should be defined only in accordance with the following claims and their equivalents.

[0154] The claims of this application are different from those of the parent application or other related applications. Therefore, the applicant revokes the disclaimer of claims made in the parent application or prior application in connection with this application. The examiner is therefore advised that such prior disclaimers and the citations made to avoid them should be reconsidered. Furthermore, the examiner is also advised that the disclaimers in this application should not be read in or against the parent application.

[0155] All patents and published applications cited above are incorporated herein by reference in their entirety.

Claims

1. An ultraviolet (UV) cured patterned film deposited on a substrate, the patterned film comprising about 60 wt % to about 95 wt % nanostructures and one or more UV curable monomers.

2. The one or more UV curable monomers may be poly(methyl (meth)acrylate), poly(ethylene glycol phenyl (meth)acrylate), poly(di(ethylene glycol) methyl ether (meth)acrylate), poly(diethylene glycol monoethyl ether acrylate), poly(ethylene glycol methyl ether (meth)acrylate), poly(1,3-butylene glycol di(meth)acrylate), poly(polyethylene glycol di(meth)acrylate), poly(1,6-hexanediol diacrylate), poly(isoboromylacrylamide), poly(isobutylene glycol di(meth)acrylate ... acrylate), poly(tetrahydrofurfuryl acrylate), poly(lauryl acrylate), poly(tricyclodecane dimethanol diacrylate), poly(glycerol triacrylate), poly(1,1,1-trimethylolpropane triacrylate), poly(pentaerythritol tetraacrylate), poly(bistrimethylolpropane tetraacrylate), poly(dipentaerythritol pentaacrylate), poly(pentaerythritol triacrylate), poly(pentaerythritol tetraacrylate), poly(trimethylol poly(1,1,1-trimethylolpropane triacrylate), poly(dipentaerythritol pentaacrylate ester), poly(isobornyl methacrylate), poly(tetrahydrofurfuryl methacrylate), poly(lauryl methacrylate), poly(tricyclodecane dimethanol dimethacrylate), poly(glycerol trimethacrylate), poly(1,1,1-trimethylolpropane trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(bistrimethylolpropane tetrameth ... poly(pentaerythritol trimethacrylate), poly(pentaerythritol tetramethacrylate), poly(trimethylolpropane trimethacrylate), poly(dipentaerythritol pentamethacrylate ester), poly(1,6-hexanediol dimethacrylate), poly(1,4-butanediol diacrylate), poly(1,9-nonanediol diacrylate), poly(1,4-butanediol dimethacrylate), poly(1,9-nonanediol dimethacrylate), or combinations thereof; The film of claim 1.

3. the film further comprises one or more photoinitiators; The film according to claim 1 or 2.

4. The film is (a) depositing onto a substrate a solution comprising nanostructures, one or more UV curable monomers, a photoinitiator, and one or more solvents, wherein the weight ratio of nanostructures to one or more UV curable monomers is from about 20:1 to about 1.5:1; (b) evaporating the one or more solvents to obtain a film comprising the nanostructures, the one or more UV curable monomers, and a photoinitiator; (c) applying a photomask to the substrate; (d) irradiating the substrate with ultraviolet light; (e) removing the photomask; and (f) washing the substrate with one or more solvents to obtain a patterned film; Manufactured by The film according to any one of claims 1 to 3.

5. the weight ratio of said nanostructures to said one or more UV curable monomers is from about 14:1 to about 6:1; The film of claim 4.

6. the one or more UV curable monomers are acrylate monomers; The film according to claim 4 or 5.

7. The acrylate monomer is 1,6-hexanediol diacrylate. The film of claim 6.

8. The film obtained in (b) comprises about 0.1 wt % to about 0.3 wt % of a photopolymerization initiator based on the total weight of the one or more UV-curable monomers; The film according to any one of claims 4 to 7.

9. The photopolymerization initiator is ethylphenyl(2,4,6-trimethylbenzoyl)phosphinate (TPO-L). The film according to any one of claims 4 to 7.

10. The irradiation in (d) is about 530 mJ / cm 2 is 365 nm ultraviolet light in an amount of The film according to any one of claims 4 to 9.

11. the one or more solvents being toluene; The film according to any one of claims 4 to 10.

12. The nanostructures are quantum dots. The film according to any one of claims 1 to 11.

13. The nanostructures include polyethylene glycol-based ligands. The film according to any one of claims 1 to 12.

14. The film is insoluble in toluene. The film according to any one of claims 1 to 12.

15. The film has a quantum yield (QY) of about 35% to about 50%. The film according to any one of claims 1 to 14.

16. A film comprising the film according to any one of claims 1 to 15. Electroluminescent device.

17. 17. The electroluminescent device of claim 16, wherein the electroluminescent device has a maximum external quantum efficiency (EQE) of about 3.75% to about 5.25%.

18. The electroluminescent device has a brightness of about 4,000 cd / m 2 to about 9,000 cd / m 2 having a maximum brightness of 18. An electroluminescent device according to claim 16 or 17.

19. the electroluminescent device has a lifetime of about 8.5 hours to about 20.5 hours at 1,000 nits; An electroluminescent device according to any one of claims 16 to 18.

20. the electroluminescent device has a lifetime of about 500 hours to about 1,300 hours at 100 nits; 20. An electroluminescent device according to any one of claims 16 to 19.

21. The film pattern is a pixel pattern. An electroluminescent device according to any one of the preceding claims.